TRADISI INTELEKTUAL ULAMA JAWA: SEJARAH SOSIAL INTELEKTUAL PEMIKIRAN KEISLAMAN KIAI SHALEH DARAT - Shokheh, Mukhamad (Paramita: Historical Studies Journal, 2011)
Kiai Shaleh Darat including one of the scholars of Islamic intellectual tradition of Java developers in a productive period of pre-modernism.ÃÂ The main work of scholars in the field of fiqh Shaleh Darat is a book Majmooat al-Sharia al-Kafiyat li al-Awam a Javanese language books of fiqh in Arabic Pegon lettered.ÃÂ Socio-political conditions of Java in the late 19th century, showed the majority of its people are Muslims who lay in religious understanding who are under control of the colonial goverment.ÃÂ This is the background for Kiai Shaleh Darat in writing the book in local language.ÃÂ Book Majmooat al-shariah al-Kafiyat li al-Awam is one book that was written by Kiai Saleh Darat.ÃÂ This book explains the basics of Islam, such as the nature of Islamic religion, faith and charity, fiqhiyah theories, such as purification, prayers, alms, fasting and rituals of hajj.ÃÂ Mu `amalat issues were also discussed such as buying and selling, usury, marriage.ÃÂ Based on the results of this study, it is concluded that Kiai Shaleh DaratÃ¢â¬â¢s thought was influential enough, both among his scholar and society in general. Keywords: intellectual tradition, scholars, Islamic Thought ÃÂ  Kiai Shaleh Darat termasuk salah satu ulama pembangun tradisi intelektual Islam Jawa pada periode pra modernisme yang produktif. Karya utama Kiai Shaleh Darat dalam bidang fiqh adalah kitab MajmuÃ¢â¬â¢at al-Syariat al-Kafiyat li al-AwamÃÂ  sebuah kitab fiqh berbahasa Jawa berhuruf Arab Pegon. Kondisi sosial politik Jawa pada akhir abad ke-19 memperlihatkan mayoritas masyarakatnya adalah muslim yangÃÂ  awam dalam pemahaman keagamaan yang berada dibawah penguasaan pemerintah kolonial. Hal inilah yangÃÂ  mendasari Kiai Saleh Darat menulis kitab dengan bahasa lokal. Kitab MajmuÃ¢â¬â¢at al-syariÃ¢â¬â¢ah al-Kafiyat li al-Awam merupakan salah satu kitab yang ditulis Kiai Saleh Darat. Kitab ini menerangkan dasar-dasar agama Islam, seperti hakikat agama Islam, iman dan ihsan, teori-teori fiqhiyah, seperti bersuci, shalat, zakat, puasa dan manasik haji. Masalah-masalah muÃ¢â¬â¢amalat juga dibahas seperti jual beli, riba, pernikahan. Berdasarkan hasil penelitian ini disimpulkan bahwa pemikiran Kiai Saleh Darat cukup berpengaruh, baik dikalangan santrinya maupun masyarakat secara umum. Kata kunci: Tradisi intelektual, ulama, Pemikiran Islam ÃÂ  ÃÂ